Society of cardiothoracic surgery in great Britain and Ireland guidance for adult mitral valve disease and interventions - Rana Sayeed; Hunaid A Vohra; Narain Moorjani; Samuel Burton; Rashmi Yadav (BMJ Surgery, Interventions, & Health Technologies)
The Society of Cardiothoracic Surgery (SCTS) in Great Britain and Ireland provides comprehensive guidelines for the management of adult mitral valve disease, addressing both surgical and transcatheter interventions. These guidelines serve as a resource for healthcare professionals, supplementing existing clinical guidelines. They emphasize the evolving complexity of mitral valve disease management, influenced by the development of new technologies, ongoing research, and randomized trials.The guidelines detail a thorough methodology, incorporating an extensive literature review and evidence assessment conducted by a clinical guidelines team. They outline best practices of preinterventional patient assessment and indications of mitral interventions, while considering the management of patient comorbidities and concomitant diseases. Detailed repair techniques for mitral regurgitation and rheumatic valve disease are provided, along with a summary of indications for emerging transcatheter and hybrid procedures, including transcatheter edge-to-edge repair, transapical neo-chordee placement, transcatheter aortic valve mitral implantation, and percutaneous mitral annuloplasty. The guidelines address postoperative mitral complications and prosthesis considerations, including up-to-date recommendations for antithrombotic management.These guidelines aim to improve patient outcomes through detailed, evidence-based recommendations and encourage the development of specialized mitral MDTs within UK practice. They provide an educational resource, clarifying the implementation of recent technologies and supporting clinical decision-making in the management of adult mitral valve disease.